A note on the geometry of Shanken's CSR T2 test for mean/variance efficiency - Roll, R (Journal of Financial Economics, 1985)
Shanken (1985) derives a test for the zero-beta capital asset pricing model (CAPM) which, as he points out, is equivalent to a test of the mean/variance efficiency of the market portfolio. This note illustrates the geometry of Shanken's test in the mean/variance space.